1977
DOI: 10.1007/bf01261508
|View full text |Cite
|
Sign up to set email alerts
|

Lack of evidence for glial cells originating from the external granular layer in mouse cerebellum

Abstract: In 25 day mice cerebella, a quantitative electron microscopic analysis showed that glial cells were not seen among 749 cells counted in the molecular layer. Likewise, a light microscopic autoradiographic study showed that labelled oligodendroglia and/or astroglia in the cerebellum were not derived from the external granular layer (EGL). Previous claims, that these cells derived from the EGL, may have arisen because other cell types, i.e., endothelial cells, pericytes, microglia, and other ectopic granule cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…We have also concluded from previous stud ies with an oligodendrocyte marker [14][15][16][17] that cerebellar oligodendrocytes do not orig inate from EGL stem cells. Our results would confirm the hypothesis of Ramon y Cajal [30] and the observations of Del Cerro and Snider [10] and Swarz and Del Cerro [33] suggesting that glial cells do not derive from the EGL. Autoradiography experiments with labelled thymidine for assessing the exact birth date of astrocytes are in progress.…”
Section: Discussionsupporting
confidence: 82%
“…We have also concluded from previous stud ies with an oligodendrocyte marker [14][15][16][17] that cerebellar oligodendrocytes do not orig inate from EGL stem cells. Our results would confirm the hypothesis of Ramon y Cajal [30] and the observations of Del Cerro and Snider [10] and Swarz and Del Cerro [33] suggesting that glial cells do not derive from the EGL. Autoradiography experiments with labelled thymidine for assessing the exact birth date of astrocytes are in progress.…”
Section: Discussionsupporting
confidence: 82%
“…Scale bar 5 653 µm for A-E, 595 µm for F, G. ule cells derived from postnatal mice (Gao et al, 1991). In the present study, EGF-R mRNA was detected within the cerebellar external granule cell layer (EGL), which has been reported to generate only neurons (Swarz and Del, 1977), making a role in neurogenesis likely. Hybridization of EGF-R cRNA in the EGL was present as early as the EGL itself was detectable, and our prior study indicated that this hybridization persists throughout the postnatal period of granule cell proliferation .…”
Section: Potential Functions Of Egf-rmentioning
confidence: 87%
“…The mRNA for EGF-R has also been localized within some of these areas (Kaser et al, 1992;Seroogy et al, 1994), but is additionally present within the proliferative germinal zones (gz) of the postnatal brain . These germinal zones include the subventricular zone (svz) of the neostriatum, which primarily produces glia during postnatal periods, as well as the external granule cell layer of the cerebellum (EGL), which produces neurons exclusively (Swarz and Del, 1977).…”
mentioning
confidence: 99%
“…The area of the molecular layer was measured as described above and thus the total number of cell profiles in the nodulus and culmen of a vermis section was calculated. Since (a) very few glia or cell types other than basket and stellate cells are normally seen in the molecular layer [19,26], (b) gliosis was not prominent in 25-day-old MAM-treated animals, and (c) most granule cells migrated to the internal granular layer following MAM treatment, this measurement provides an estimate of the number of basket and stellate cell profiles. The estimate is more likely to be slightly high for MAMtreated animals than for control animals due to the greater probability of other cell types in the molecular layer.…”
Section: Morphological Studiesmentioning
confidence: 99%